Producción y comercialización de un licor a base de caña de azúcar con frutas tropicales dirigido al mercado de Guayaquil - Navia Moran, Vanessa (2009)
This new and innovative pro duct (sugar cune liquor with tropicalfruits) search of some form to sat isfy and to specifytheidea ofthepopularones "guarapos"thataresoldintheEcuadorianmountain,insuchawaythat all have access to this traditional drink. Thefirst step to carry out is a market study in that a detailed explanation of the product will be given which we will offer andofthemarkettothe onethat plantoenter,animperious anddetailedanalysisof theenvironment ofthis marketwillbemadetherefore,by means ofastudy oftheexistentdemandandthiswtrytobeabletodeterminethe preferences and consumer tastes and to analyze the possibility that our new product satisfies this demand; likewise wewillstudy theoffer,asourpossiblecompetitors,the prices fixedbythemarket andthe differentmeansinthose that we will make arrive "Let it be. " Another important point in our investigation is the goo d distribution of the pro duct, the readiness of the raw material and the cost that this will represent us, helshe will also take in considerationthediflerentproductiveprocessesfortheelaborationof theproduct, likewisetherequiredhuman personnel to develop it. Lastly it will be carried out afinancial study to analyze that so viable it is the project and this lI'ay to be able to determine the profitability that youlthey will be able to obtain the investors.